Eksplorasi Komunikasi Korporasi Efektif dalam Keberlangsungan Program Corporate Social Responsibility di PT. PLN Unit Induk Distribusi Sumatera Utara - Khairani, Dewi Suci (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
One company that has implemented corporate social responsibility is PT. PLN (Persero) which is a State-Owned Enterprise (BUMN) which manages all aspects of electricity in Indonesia. PLN is determined to harmonize the development of the three aspects of electricity supply, namely economic, social and environmental. For this reason, PLN developed a Corporate Social Responsibility (CSR) Program as a concrete manifestation of corporate responsibility. Effective communication is needed to be able to manage and minimize communication problems that occur internally and externally to the company. The results of this research are that there is effective corporate communication in the implementation of sustainable CSR programs, including internal communication which includes upward, downward and horizontal communication. Also external communication that utilizes media and pays attention to the feedback provided.